A novel serum microRNA-based identification and classification biomarker of human glioma - Wenli Xing; Chun Zeng (Tumor Biology)
Malignant glioma is one of the most common primary brain tumors that develop via multiple pathways and gene deregulation. MicroRNAs are involved in human cancer development and progression, and their serum expression profiles of glioma patients may be useful for classifying cancers. However, the profile and molecular mechanism of serum microRNAs for human glioma are poorly understood. Thus, it is crucial to analyze microRNA expression in human glioma serum to identify molecular subclasses and early stage of glioma. In this study, we performed microRNA alteration that contributes to glioma profile via analysis of The Cancer Genome Atlas RNA sequencing data and other independent Gene Expression Omnibus microarray data. We identified the glioma-associated novel microRNA as a key regulator of human glioma development and progression. The putative novel miR-1825 was validated by real-time polymerase chain reaction and its expression was significantly decreased in the serum of glioma patients compared with healthy controls. Patients with high miR-1825 expression had a longer survival rate. Interestingly, we found that miR-1825 expression levels were dependent on tumor size and pathological grading in glioma patients, but not associated with other factors including age and T classification. MicroRNA–Gene Ontology network indicated that miR-1825 may play an important role in the development of human glioma including apoptosis, cell proliferation, and invasion. In vitro assays of miR-1825 inhibit U87 cell proliferation and invasion and induce apoptosis. Furthermore, we provide evidence that the tumor-suppressive microRNA miR-1825 controls KLF2 expression. Reporter gene analyses revealed that both microRNAs directly targeted the 3′-untranslated region of KLF2 messenger RNA. These data demonstrated that miR-1825 expression in serum of human glioma was associated with tumorigenesis and miR-1825 may be used as a biomarker for identification of the pathological grade of glioma.